2015
DOI: 10.1016/s2215-0366(14)00049-2
|View full text |Cite
|
Sign up to set email alerts
|

An online programme to reduce depression in patients with multiple sclerosis: a randomised controlled trial

Abstract: (2015) An online programme to reduce depression in patients with multiple sclerosis: a randomised controlled trial. The Lancet Psychiatry, 2 (3). pp. 217 223. ISSN 2215 0366It is advisable to refer to the publisher's version if you intend to cite from the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 37 publications
3
136
2
3
Order By: Relevance
“…However, as patients with psychosis often do not receive specific treatment for depression, the potential of the program may be higher than in conventional (depression) populations who are usually not naïve about the contents of such programs. In linewith this, themagnitude of the effect of online interventions for depressionwasmoderate for a group of neurological patients in two recent studies of whom most had never received specific treatment for depression before (Fischer et al, 2015;Schröder et al, 2014). Based on the assumption that depressive symptoms and depression-related cognitions (e.g., worry thinking style, negative beliefs about the self, interpersonal sensitivity, sleep disturbance) play a causal role for the emergence of positive symptoms (Garety et al, 2001;Freeman and Garety, 2014;Lincoln et al, 2014),we also expected the treatment to impact on positive symptoms.…”
Section: The Present Studymentioning
confidence: 70%
“…However, as patients with psychosis often do not receive specific treatment for depression, the potential of the program may be higher than in conventional (depression) populations who are usually not naïve about the contents of such programs. In linewith this, themagnitude of the effect of online interventions for depressionwasmoderate for a group of neurological patients in two recent studies of whom most had never received specific treatment for depression before (Fischer et al, 2015;Schröder et al, 2014). Based on the assumption that depressive symptoms and depression-related cognitions (e.g., worry thinking style, negative beliefs about the self, interpersonal sensitivity, sleep disturbance) play a causal role for the emergence of positive symptoms (Garety et al, 2001;Freeman and Garety, 2014;Lincoln et al, 2014),we also expected the treatment to impact on positive symptoms.…”
Section: The Present Studymentioning
confidence: 70%
“…19 One RCT evaluated this form of therapy for depression in 255 patients with diabetes. 16 The program consisted of eight lessons delivered over eight weeks, and measurements were taken at baseline, immediately after treatment and one month later.…”
Section: Physical Illnessmentioning
confidence: 99%
“…19 The program included 10 sequential modules, with patients assessed at baseline, immediately after treatment and at six-month follow-up. The effect size for the total Beck Depression Inventory score was 0.53 (p = 0.01) compared with waitlisted controls, based on intention-to-treat analysis (n = 90).…”
Section: Physical Illnessmentioning
confidence: 99%
“…In light of the success of telephone-administered interventions for improving various MSassociated symptoms and quality of life [76][77][78][79][80], several studies have examined (or will examine) whether interactive telehealth interventions can improve MS-associated anxiety, cognitive function, mood, fatigue, impact, pain, quality of life, and sleep quality [81][82][83][84][85][86][87][88].…”
Section: Problem Solving Skills For Persons With Ms (Mapss-ms) Programentioning
confidence: 99%
“…These include: an online self-help program (Deprexis) that combines cognitive behavioral therapy (CBT) with mobile platform and dialog technology, and has proven efficacy in treating depression [85,89]; an Internet-based CBT program (MS Invigor8) administered with or without email support to help reduce fatigue symptoms [86,87]; MS-specific multimedia software that delivers a meditation course designed to decrease anxiety, depression, and fatigue, and improve quality of sleep, and quality of life [83]; the project Guidelines for Exercise in MS, an interactive, guidelines-based exercise program aimed at improving MS symptoms and quality of life [88]; and physical exercise e-training programs that demonstrate positive and significant effects on muscle strength, lung function, and sports activity, but not on quality of life or fatigue [90,91]. Perhaps the most robust of these studies was a 9-week randomized trial conducted in patients with MS who had self-reported depression symptoms (N = 90) [85].…”
Section: Problem Solving Skills For Persons With Ms (Mapss-ms) Programentioning
confidence: 99%